Re-presenting Research - Sterk, Florentine Marnel; van Goch, Merel M. (Springer Nature, 2023)
This open access book focuses on the textual features, or ‘strategies’, which form popularization discourse. In popularization discourse, research findings from academia are re-presented to make them noteworthy to society and influential for everyday life. Popularization involves recontextualization, or reimagination of findings in an everyday and newsworthy context, and reformulation, the use of audience-appropriate language to increase text comprehension and engagement. ‘Re-presenting research’ presents an empirically grounded, analytic framework for the analysis of popularization texts. Its applicability spans across disciplinary, multidisciplinary, and interdisciplinary fields, and overarches science communication, science journalism, and research communication. The book offers theoretical background information on popularization discourse, empirical underpinning of the construction of the framework, and practical applicability in examples from multiple text types and academic fields. This book acts as a guide for those working with or on popularization discourse – whether it is to analyze it or learn about it.